Traditional theories of development versus the theory of symbolic sites of belonging - Wafa Hazaymeh, Mastur Rehim, Rana Alsalaymeh, (Opción, 2020)
The study aims to investigate traditional theories of development versus the theory of symbolic sites of belonging via comparative qualitative research methods. As a result, globalization is the abolition of people’s identities in favor of one nation or rather one system, which has a lot of mechanisms of robbery and predominance. In conclusion, the concepts of modern colonialism and dependency of the West are no longer convincing to interpret the reasons for the failure of developmental efforts, but it necessary to expand problems to include intellectual, cultural and social components.